KESESUAIAN (CONGRUENCY) TIPE KEPRIBADIAN DENGAN PILIHAN PROGAM STUDI (Penelitian Deskriptif Pada Mahasiswa Fakultas Psikologi Angkatan 2012/2013 UIN Sunan Gunung Djati Bandung) - Nani Nuranisah Djamal (Psympathic : Jurnal Ilmiah Psikologi, 2014)
The phenomenon of error in choosing courses are still quite common among college students and had impact on the low of learning achievement, a long process of study completion, and in the further is the lack of absorption of graduates in the work field. The aim of this study was to obtain empirical description about: personality type, the fit between personality type with a choice of courses, gender differences in terms of suitability factor personality type with a choice of courses as well as the achievements of the appropriate classification of personality types. This descriptive study used sample of students of the Faculty of Psychology class of 2012/2013 UIN Sunan Gunung Djati Bandung numbered 144 students. Measurement of the personality type had used Holland’s personality inventory. The study results showed that: 1) the majority of students (70.17%) had a personality type that is incompatible with the psychology courses, 2) gender factors has influence the choice of study program, 3) The fit between personality type along with a choice of courses have effect on the acquisition of a better performance